Collective cell migration during optic cup formation features changing cell-matrix interactions linked to matrix topology - Soans, Karen G.; Ramos, Ana Patricia; Sidhaye, Jaydeep; Krishna, Abhijeet; Solomatina, Anastasia; Hoffmann, Karl B.; Schlüßler, Raimund; Guck, Jochen; Sbalzarini, Ivo F.; Modes, Carl D.; Norden, Caren (Current Biology, 2022)
Cell migration is crucial for organismal development and shapes organisms in health and disease. Although a lot of research has revealed the role of intracellular components and extracellular signaling in driving single and collective cell migration, the influence of physical properties of the tissue and the environment on migration phenomena in vivo remains less explored. In particular, the role of the extracellular matrix (ECM), which many cells move upon, is currently unclear. To overcome this gap, we use zebrafish optic cup formation, and by combining novel transgenic lines and image analysis pipelines, we study how ECM properties influence cell migration in vivo. We show that collectively migrating rim cells actively move over an immobile extracellular matrix. These cell movements require cryptic lamellipodia that are extended in the direction of migration. Quantitative analysis of matrix properties revealed that the topology of the matrix changes along the migration path. These changes in matrix topologies are accompanied by changes in the dynamics of cell-matrix interactions. Experiments and theoretical modeling suggest that matrix porosity could be linked to efficient migration. Indeed, interfering with matrix topology by increasing its porosity results in a loss of cryptic lamellipodia, less-directed cell-matrix interactions, and overall inefficient migration. Thus, matrix topology is linked to the dynamics of cell-matrix interactions and the efficiency of directed collective rim cell migration during vertebrate optic cup morphogenesis.
CRIS-Team Scopus Importer:2023-03-23
Keywords: optic cup; collective cell migration; matrix topology; zebrafish; topology simulation